Wittgenstein's metaphilosophy - Horwich, Paul. (Oxford : Oxford University Press, 2013)
A bold interpretation of Ludwig Wittgenstein's later work. It argues that it is Wittgenstein's radically anti-theoretical metaphilosophy - and not his identification of the meaning of a word with its use - that underpins his discussions of specific issues concerning language, the mind, mathematics, knowledge art, and religion.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.